PENGARUH KARAKTERISTIK WIRAUSAHA DAN KECANGGIHAN TEKNOLOGI TERHADAP KINERJA USAHA MIKRO DAN MENENGAH (UMKM) DI KECAMATAN SUKASADA - Usada Putra, Made Wahyu; Suardika, I Ketut (Komunitas Manajemen Kompetitif, 2024)
This study aims to determine the influence of entrepreneurial characteristics and technological sophistication on the performance of micro and small-medium enterprises (MSMEs) in the Sukasada District. The study employs a quantitative approach with data collection conducted through questionnaires. The analytical technique utilized in this research is multiple linear regression analysis. The results indicate that entrepreneurial characteristics significantly affect the performance of MSMEs in the Sukasada District, demonstrating a direct and strong relationship between entrepreneurial characteristics and MSME performance. This is supported by hypothesis testing using the T-Test, where the obtained t-value is greater than the critical t-value, thus accepting the hypothesis. Technological sophistication also influences the performance of MSMEs in the Sukasada District, showing a direct and strong relationship between technological sophistication and MSME performance. This is likewise supported by hypothesis testing using the T-Test, where the obtained t-value is greater than the critical t-value, resulting in the acceptance of the hypothesis.